Immediate neural effects of acupuncture manipulation time for stroke with motor dysfunction: a fMRI pilot study - Zhou, Yihao; Dai, Anhong; Feng, Sifeng; Zhu, Tao; Liu, Meifang; Shi, Jing; Wang, Dongyan (Frontiers in Neuroscience, 2024)
Introduction: Acupuncture is widely utilized as a beneficial intervention for the treatment of motor dysfunction after stroke, and its effectiveness depends on the stimulation dose. Manipulation time is an important factor affecting the dose. This trial aimed use fMRI to explore the immediate neural effects in stroke patients with motor dysfunction by different acupuncture manipulation times, to reveal the neural mechanism of acupuncture manipulation. Methods: Thirty participants were divided into three groups according to different acupuncture times. Each group received the same acupoint prescription, although the continuous manipulation time of each acupoint in three groups was 1-minute, 2-minute and 3-minute, respectively. The NIHSS, FMA and fMRI-BOLD in each participant we obtained before and after acupuncture manipulation. Then, we used the regional homogeneity (ReHo) algorithm to analyze the changes of brain function and to compare the neural effects at different acupuncture manipulation times. Results: There were no significant differences in NIHSS and FMA scores between and within groups. Longitudinal analysis of ReHo values indicated that the right inferior frontal gyrus was activated in the 1-minute group, the right insula in the 2-minute group, and the right inferior temporal gyrus in the 3-minute group. Compared with the 1-minute group, the 2-minute group showed the ReHo values of the right precentral gyrus was decreased, and the 3-minute group showed the left cerebellum posterior lobe was increased, the right posterior cingulate gyrus and the right anterior cingulate gyrus were decreased. Compared with the 2-minute group, the 3-minute group showed the ReHo values of the right cerebellum anterior lobe was increased. Conclusion: Our findings suggest that acupuncture at different manipulation times caused different changes of the neural effects in stroke patients, and the volume of activated voxel clusters is positively correlated with the manipulation time. Longer acupuncture manipulation could drive SMN and DMN in stroke patients, which may be the potential neurological mechanism of acupuncture manipulation affecting the recovery of motor dysfunction.